Arithmetik der Körper: 21.10. bis 27.10.1990 - Yardēn, Moše; Roquette, Peter (Tagungsbericht, 1990)
Serban A. Basarab; Eberhard Becker; Luc Belair; Zoe Chatzidakis; Gregory L. Cherlin; Francoise Delon; Lou van den Dries; Ido Efrat; Gerhard Frey; Michael David Fried; Wulf-Dieter Geyer; Barry William Green; Dan Haran; Moshe Jarden; Wolfram Jehne; Ivan Kausz; Norbert Klingen; Jochen Koenigsmann; Franz-Viktor Kuhlmann; Luc Lauwers; Angus John MacIntyre; Margarita Otero Dominguez; Johan Pas; Florian Pop; Alexander Prestel; Jürgen Ritter; Peter Roquette; Michael Spieß; Helmut Völklein; Alfred Weiss
Keywords: Konferenzschrift